2018
DOI: 10.1039/c8ra07571a
|View full text |Cite
|
Sign up to set email alerts
|

Study on the growth rate of natural gas hydrate in water-in-oil emulsion system using a high-pressure flow loop

Abstract: Hydrate slurry transport technology in deep-water pipelines has become a focal point among worldwide researches, due to its high economic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(44 reference statements)
0
8
1
Order By: Relevance
“…Contrary to this result in the present study, Lv et al. , reported that the hydrate formation in the later stage is inhibited at a higher water flow rate because the gas‐liquid interface is covered by the formed hydrate, by promotion of the mass transfer. In this study, the decreasing trend of the hydrate formation rate was not observed.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to this result in the present study, Lv et al. , reported that the hydrate formation in the later stage is inhibited at a higher water flow rate because the gas‐liquid interface is covered by the formed hydrate, by promotion of the mass transfer. In this study, the decreasing trend of the hydrate formation rate was not observed.…”
Section: Resultscontrasting
confidence: 99%
“…The driving force for gas hydrate growth can be increased by lowering the temperature (e.g., Taylor et al, 2007), which decreases methane solubility in water in the presence of hydrate (Lu et al, 2008; Servio & Englezos, 2002; Subramanian & Sloan, 2002) and thereby increases the amount of excess dissolved phase methane that can then be used for gas hydrate formation. The driving force can also be increased by raising the pressure (e.g., Lv et al, 2018), which dissolves more gas into the water. Cooling the system by a few degrees is far more effective at driving increased hydrate formation than is increasing pressure by a few MPa (1 MPa is roughly equivalent to 100 m of water in the marine environment).…”
Section: Rates Of Hydrate Phase Transitionsmentioning
confidence: 99%
“…Here, the influence of oil cut also can be justified. According to the literature, oil cut plays a very minute role in gas hydrate formation/dissociation studies in oil–water emulsions compared to that of water cut. The increase in oil cuts in the system increases the inhibition of gas hydrate formation. This is due to the presence of a mixture of various inhibition mechanisms and possibly a rivalry between mechanisms for inhibition promotion …”
Section: Resultsmentioning
confidence: 99%